Advancements and challenges in design of flow field plates in proton exchange membrane fuel cells: a comprehensive review - Merdjani, Abdelhakim; Kizilova, Natalia; Awotwe, Tabbi Wilberforce; Kostrzewski, Mariusz (Frontiers in Energy Research, 2025)
Proton Exchange Membrane Fuel Cells (PEMFCs) have received increasing attention as a renewable energy technology with the potential to reduce greenhouse gas emissions and reduce reliance on fossil fuels. This review presents the advancements and challenges associated with flow field plates (FFPs) and cooling systems in PEMFC with a particular emphasis on the exploration and integration of bio-inspired designs which inspiration from natural structures offers unique solutions for uniformity of fuel and heat distribution. A comparative study on the innovative nature-inspired designs and conventional designs for FFPs and cooling systems is presented. Various fabrication methods of FFPs assessing their feasibility and economic implications are discussed. The comparative analysis aims to offer a holistic view on the current landscape and future directions in PEMFC technology, highlighting the importance of efficient design and manufacturing strategies to meet the growing demands for sustainable and efficient energy solutions.